Respuesta :
Answer: [tex]x = -10[/tex]
Step-by-step explanation:
Hey there! I hope these steps will help you accomplish this problem :)
Step 1: Remove the parentheses.
[tex]6x - 2x + 9 = -31[/tex]
Step 2: Simplify.
[tex]6x - 2x + 9[/tex] to [tex]4x + 9[/tex].
[tex]4x + 9 = -31[/tex]
Step 3: Subtract 9 from both of the sides.
[tex]4x = -31 - 9[/tex]
Step 4: Simplify.
[tex]-31 - 9[/tex] to [tex]-40[/tex].
[tex]4x = -40[/tex]
Step 5: Divide both of the sides by 4.
[tex]x = -\frac{40}{4}[/tex]
Step 6: Simplify.
[tex]\frac{40}{4}[/tex] to [tex]10[/tex].
[tex]x = -10[/tex]
Answer:
Step-by-step explanation:
Here you go mate
step 1
6x-(2x-9)=-31 equation
step 2
6x-(2x-9)=-31 simplify
6x+-1(2x-9)=-31
step 3
6x+(-1)(2x-9)=-31 distribute
6x+-1(2x)+(-1)(-9)=-31
6x+-2x+9=-31
step 4
(6x+-2x)+(9)=-31 combine the terms that are alike
4x+9=-31
step 5
4x+9(-9)=−31(-9) subtract-9
4x=-40
step 6
4x/4=-40/4 divide by 4 because 4 is a number that can make the division easier
answer
x=-10